Transactional Associations between Children’s Socioemotional Difficulties and Parental Aggression toward the Child over a Ten-Year Period in a Lower-Income Population - Langevin, Rachel (Journal of family violence, 2021)
This study examined the transactional effects of parental physical and verbal aggression and children’s externalizing (EP) and internalizing problems (IP) from early school age to adolescence in lower-income community sample using a multi-informant perspective. Mother-child dyads (n = 175) from urban low socioeconomic backgrounds that are part of the Concordia Longitudinal Research Project, a prospective intergenerational study, participated. Children’s EP and IP were assessed by mothers and teachers at ages 6–8, 9–11, and 13–17-years-old (Child Behavior Checklist). Mothers also self-reported physical and verbal aggression toward their child (Conflict Tactics Scales Parent-Child). Results from cross-lagged analyses with mothers’ reports of EP and IP revealed a transactional process with EP and physical aggression, and a child-driven effect with IP and verbal aggression. EP at 6–8-years-old were associated with increased physical aggression at 9–11 years of age, that in turn were associated with increased EP in adolescence. IP at 6–8 years old were associated with increased verbal aggression at 9–11 years. Some effects were identified when using teachers’ reports of socioemotional difficulties, including a transactional process from verbal aggression at 6–8 years old, to increased EP at 9–11 years, to increased physical aggression at 13–17 years. Overall, parent-driven and child-driven effects were present, but results differed across informants and behaviour problem types. These results have important implications for research and intervention that are discussed in light of the developmental psychopathology and transactional models of development.